Electron accepting capacity of dissolved and particulate organic matter control CO2 and CH4 formation in peat soils. (15th January 2019) - Gao, Chuanyu; Sander, Michael; Agethen, Svenja; Knorr, Klaus-Holger
Abstract: Peatlands are a major source of atmospheric CH4 . The availability of terminal electron acceptors largely affects the ratio of CO2 to CH4 formation under water-logged anoxic conditions in these systems. Although the importance of peat organic matter as an electron acceptor is increasingly recognized, the actual budgets of electron accepting capacities of dissolved and particulate organic matter remain poorly characterized. To address this research need, we incubated three different peat materials and linked changes in the electron accepting capacities (EAC) of peat organic matter (OM), including dissolved and particulate organic matter, to the observed CO2 and CH4 formation. Under anaerobic conditions, EACOM decreased inverse to non-methanogenic CO2 formation. Only after utilizable EACOM was depleted did strictly methanogenic conditions evolve with equimolar CH4 and CO2 formation rates, as theoretically expected. The reduction of OM and the resultant decrease in EACOM explained between 26 and 56% of the non-methanogenic CO2, which was between 5 and 39% of total CO2 produced. Compared to EACPOM, EACDOM remained constant and may have served as a mediator in electron transfer to the POM. In summary, our study quantitatively demonstrated the important role of peat OM as terminal electron acceptor for anaerobic respiration in organic soils.